Regionalne i lokalne ustroje polityczne. Część II - Domagała, Małgorzata; Iwanek, Jan (Studia Politicae Universitatis Silesiensis, 2017)
Abstract: Regional and local political systems. Part II The systemic diversity of the regions and local units can be subsumed to three possible forms of political systems: 1) self‑government, 2) territorial autonomy and 3) the federal state. Based upon that criterion, modern democratic states can be divided into: 1) unitary states with self‑government, 2) unitary states with territorial autonomy and self‑government, 3) federal states with self‑government, 4) federal states with territorial autonomy and self‑government. That division clearly points to the fact, that unitary and federal states can successfully exhibit the same types of political systems on the regional and local levels: territorial autonomy and self‑government. In consequence, both federal and unitary states, under this particular respect, do not exhibit differences. The systems present in the unit‑parts of a federation (regardless of their designation: republics, states, lands, cantons or provinces) in themselves are not a separate category and form of the political system, but form together with others, the three subcentral legal‑political systems present in democratic states. However, the understanding of federalism as concept referring to something more than the legal‑political system of a given state (or even the political system sensu stricto) might seems unconvincing, but still in the consideration of federalism one needs to step away from the analysis of existing federal states (however, comparative constitutional law and constitutional practice must have fundamental impact) and create the prognoses of systemic solutions in a group of highly decentralized unitary states. Besides that, the research of the political theory of federalism and federation presents itself as not without merit to the undertaken task. Key words: federalism, territorial autonomy, regional political system, decentralism